Sagot :
Answer:
Simplifying
2p + 15 = 21
Reorder the terms:
15 + 2p = 21
Solving
15 + 2p = 21
Solving for variable 'p'.
Move all terms containing p to the left, all other terms to the right.
Add '-15' to each side of the equation.
15 + -15 + 2p = 21 + -15
Combine like terms: 15 + -15 = 0
0 + 2p = 21 + -15
2p = 21 + -15
Combine like terms: 21 + -15 = 6
2p = 6
Divide each side by '2'.
p = 3
Simplifying
p = 3
Step-by-step explanation:
Simplifying
2p + 15 = 21
Reorder the terms:
15 + 2p = 21
Solving
15 + 2p = 21
Solving for variable 'p'.
Move all terms containing p to the left, all other terms to the right.
Add '-15' to each side of the equation.
15 + -15 + 2p = 21 + -15
Combine like terms: 15 + -15 = 0
0 + 2p = 21 + -15
2p = 21 + -15
Combine like terms: 21 + -15 = 6
2p = 6
Divide each side by '2'.
p = 3
Simplifying
p = 3